Perlindungan Hukum Terhadap Pemilik Kondominium Atas Pailitnya PT. Dwimas Andalan Bali Sebagai Pengembang - Mulyawan, Kiasnabila; Hasani, Ismail; Alam, Faris Satria (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2024)
The bankruptcy of a developer company often directly impacts condominium owners who have made a sale and purchase transaction, in the case of the bankruptcy of PT. Dwimas Andalan Bali condominium owners experience legal protection because the units that have been purchased are included in the bankruptcy estate. This study analyzes the developer's responsibility towards consumers in bankruptcy conditions and the legal status of condominium objects that are part of the bankrupt assets. The method used is normative legal research with a case approach focusing on the Supreme Court Decision Number 437 K / Pdt. Sus-Pailit / 2019. The study results show that in bankruptcy conditions, developers still have legal obligations to consumers who have fulfilled their achievements in the sale and purchase transaction. Based on Article 36 of Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations, consumers have the right to submit a request to the curator to ensure the process of extending condominium ownership rights to the Deed of Sale and Purchase (AJB) stage. Consumers are entitled to compensation or damages if these obligations are not met. In the case of developer bankruptcy, consumer rights must still be protected through available legal mechanisms, either through an application to the curator or other legal efforts. Therefore, it is necessary to strengthen legal protection for consumers so that they are not harmed in bankruptcy-related property transactions.